Fundamentals of finance : investments, corporate finance, and financial institutions - Akan, Mustafa (De Gruyter, 2020)
Finance is the study of how individuals, institutions, governments, and businesses acquire, spend, and manage their money and other financial assets to maximize their value or wealth. Fundamentals of Finance introduces the nuances of finance in a comprehensive yet concise manner and is essential reading for professionals building a career in finance or for students taking a course in finance. The book consists of four parts: Part I: "Introduction to Finance, Money and Interest Rates, and Time Value of Money" focuses on the role financial markets play in the financial system and financial basics that underlie how markets operate. Part II: "Investments and Portfolio Management" discusses the characteristics of stocks and bonds, how securities are valued, the operations of securities markets, formation of optimal portfolios, and derivatives. Part III: "Financial Management/Corporate Finance" explores financial planning, asset management, and fund-raising activities that will enhance a firm’s value. Part IV: "Management of Financial Institutions" focuses on management of financial institutions in general, and risk management in financial institutions in particular. The book’s many examples, appendices, graphs and tables provide valuable know-how to a wide audience, making it an excellent resource for professionals as well as students who wish to attain a broad understanding of finance. Please contact Stefan.Giesen@degruyter.com to request additional instructional material.